Copper triflate catalyzed Baeyer- Villiger oxidation of ketones - Duc, Dau Xuan; Nguyet, Nguyen Thi (Vietnam Journal of Science and Technology, 2019)
A simple, efficient and eco-friendly method for Baeyer-Villiger oxidation reaction has been developed. The reaction employed m-CPBA as the oxidant with Cu(OTf)2 catalyst and was carried out in CH2Cl2 at room temperature. Nine lactones and ester were obtained in excellent yield (85-94%). Furthermore, the catalyst could be reused twice without considerable loss in activity.